The role of discourses in enacting neoliberal urbanism: Understanding the relationship between ideology and discourse in planning. (February 2020) - Zanotto, Juliana M
Claims that neoliberalism has been shaping planning practice and the production of space abound in planning literature. In this article, neoliberalism is treated not only as a set of policies but also as an ideology that organizes a particular way of seeing and orients action accordingly. The article explores how a particular socially shared belief system (ideology) that is taken as common sense (naturalized) provides the basis for particular ways of talking (discourses) about planning and urban development that legitimize and justify certain actions while making alternative possibilities unthinkable. In this sense, the article focuses on ideology in action and provides an empirically grounded discussion that renders ideology visible. Thus, ideology emerges from the empirical case as an explanatory mechanism to make sense of the dominant discourse that legitimizes the proliferation of suburban gated communities in the Metropolitan Region of Curitiba, in Brazil. The deconstruction of the discourse reveals content and structural properties that combine environmental concerns and neoliberal principles to turn potentially controversial practices into desirable outcomes. The ideological nature of the discourse is revealed when alternative ways of seeing and acting challenge its commonsensical and taken for granted claims. While simplifying complex relationships and rendering important elements invisible, the discourse appeals to a wide range of actors who hold different individual and professional values. Ultimately, this article offers insights into the mechanisms through which ideologies are manifested, reproduced, and materialized in planning practice.